IMPOLITEESS STRATEGIES USED ON ONLINE COMMENTS IN THE LIPUTAN6.COM OF POLITICAL NEWS - Lisa Fitri Meidipa; Khairunnisah Lubis (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2021)
This study investigates the impoliteness strategies in online comments in Liputan6.com. The objectives of this study are: 1) to investigate the types of impoliteness strategies used on online comments in website Liputan6.com, 2) to find out the dominant type of impoliteness strategies used on online comments in website Liputan6.com. This study was conducted by using qualitative content analysis method. The data were taken from comments of internet users in five topics of political news in Idntimes.com. The finding showed that four of five types of impoliteness strategies are used on online comments in website Liputan6.com. They are: Bald on Record, Positive impoliteness, Negative Impoliteness, and Sarcasm or Mock politeness. The dominant types is negative impoliteness by used scorn or ridicules comments and invade the other's space with that comments and explicitly associate the other with a negative aspect.